A new species of the genus Aalatettix Zheng & Mao (Orthoptera, Tetrigoidea, Tetrigidae) from China - Wang, Li-Ming; Lu, Ying; Luo, Han (Zootaxa, 2021)
This paper provides a new species of the genus Aalatettix Zheng & Mao, 2002. The type specimens are deposited in the Insect Collection of College of Life Sciences, Xinyang Normal University, Xinyang, China.